AlTiSiN coating preparation method based on HiPIMS technology
The preparation of AlTiSiN coating through HiPIMS technology and gradient bias control solves the problem of insufficient coating performance of stainless steel bipolar plates, and achieves amorphous structural coating with high hardness and excellent corrosion resistance, meeting the performance requirements of DOE2024.
Patent Information
- Application Number
- CN202510547627.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-28
- Publication Date
- 2025-08-01
AI Technical Summary
In the prior art, the coating performance of stainless steel bipolar plates is insufficient, especially in acidic environments, and it is difficult to meet the performance indicators of DOE2024.
Using HiPIMS technology, TiAlSiN coating is prepared through gradient bias control, including glow cleaning on the surface of the workpiece, TiAlSi transition layer deposition and N-element surface layer deposition, gradually adjusting the interface energy to avoid stress sudden changes and columnar crystal growth, and forming an amorphous structure coating.
The prepared AlTiSiN coating has high hardness, excellent corrosion resistance and mechanical properties, with a maximum hardness of up to 16.9GPa, which significantly improves the corrosion resistance of stainless steel bipolar plates.
Smart Images

Figure CN120400772A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of coating materials, and particularly to a method for preparing an AlTiSiN coating based on HiPIMS technology. Background Art
[0002] Compared with traditional graphite bipolar plates, stainless steel bipolar plates stand out for their light weight, affordability, superior mechanical strength, low processing costs, and ease of large-scale production. Especially in an acidic environment, it shows good corrosion resistance, which makes stainless steel a highly competitive bipolar plate substrate option with great potential for large-scale promotion. In order to meet the performance indicators required by DOE2024 for bipolar plate materials, it is necessary to coat and modify the graphite bipolar plates to meet the requirements.
[0003] Corrosive fluids tend to penetrate into the material along grain boundaries, which often leads to the destruction of crystalline materials. In the prior art, a TiAlSiN nanocomposite coating has been successfully prepared by high-power pulsed magnetron sputtering technology. Compared with the TiAlSiN coating deposited by DC magnetron sputtering, the TiAlSiN coating deposited by HiPIMS technology is an amorphous coating, a nanocomposite structure with an amorphous Si3N4 interfacial phase encapsulating nitride nanocrystals, which can endow the coating with properties such as high hardness, high toughness, and excellent corrosion resistance. At the same time, due to its unique structure without grain boundaries, dislocations, and vacancies, etc., it shows more excellent corrosion resistance. Summary of the Invention
[0004] The purpose of the present invention is to provide a method for preparing an AlTiSiN coating based on HiPIMS technology. To solve the technical problem of insufficient coating performance, the present invention specifically provides the following technical solutions:
[0005] The present invention provides a method for preparing an AlTiSiN coating based on HiPIMS technology, including the following steps:
[0006] Perform glow cleaning on the surface of the workpiece;
[0007] While the workpiece revolves and rotates in the cavity, sputter a TiAlSi target onto the workpiece through HiPIMS. First, load the workpiece to the starting bias value through a bias power supply, and then gradually reduce the starting bias value to the coating bias value through the first voltage reduction treatment, and a TiAlSi surface layer is deposited on the surface of the workpiece to complete the deposition of the transition layer;
[0008] Keep the workpiece rotating, gradually introduce nitrogen into the vacuum chamber until the coating flow rate value is reached. First, load the workpiece to the starting bias voltage value through the bias power supply, and then gradually reduce the starting bias voltage value to the coating bias voltage value through the second voltage reduction process. N elements are deposited on the TiAlSi surface layer to complete the deposition of the surface layer, so as to obtain the AlTiSiN coating.
[0009] As a preferred embodiment of the present invention, in the first voltage reduction process, the starting bias voltage value is -250V, and the coating bias voltage value is -160V to -10V.
[0010] As a preferred embodiment of the present invention, the first voltage reduction process is a gradient voltage reduction, and the voltage reduction amplitude of the gradient voltage reduction is 40 - 50V;
[0011] In each gradient pressure, the unit deposition time is maintained;
[0012] The deposition time of the coating bias voltage value is greater than the unit deposition time. The deposition time of the coating bias voltage value is greater than the unit deposition time during the bias voltage drop process to achieve shallow implantation and reduce the stress mutation on the workpiece surface.
[0013] As a preferred embodiment of the present invention, in the second voltage reduction process, the starting bias voltage value is -250V, and the coating bias voltage value is -160V to -10V.
[0014] As a preferred embodiment of the present invention, the second voltage reduction process is a gradient voltage reduction, and the voltage reduction amplitude of the gradient voltage reduction is 40 - 50V; in each gradient pressure, the unit deposition time is maintained;
[0015] Similarly, in the deposition of the surface layer, the deposition time of the coating bias voltage value is greater than the unit deposition time to reduce the stress mutation on the surface layer and the workpiece surface.
[0016] As a preferred embodiment of the present invention, in the glow cleaning step, the specific parameter range of the bias power supply is: the voltage value is -600V, the frequency is 60kHz, and the duty cycle is 80%;
[0017] The cleaning time is 20min.
[0018] As a preferred embodiment of the present invention, in the coating flow rate value, the nitrogen flow rate value is 25sccm.
[0019] As a preferred embodiment of the present invention, in the glow cleaning step, the specific parameter range of the bias power supply is: the voltage value is -400V to -600V, the frequency is 20kHz to 100kHz, and the duty cycle is 20% - 80%;
[0020] The cleaning time is 10 min - 30 min.
[0021] As a preferred embodiment of the present invention, in the glow cleaning step, the specific parameter range of the bias power supply is: the voltage value is -600 V, the frequency is 60 kHz, and the duty cycle is 80%;
[0022] The cleaning time is 20 min.
[0023] The present invention has the following beneficial effects compared with the prior art:
[0024] In the present invention, hierarchical deposition is carried out during the deposition of the transition layer and the surface layer. During the deposition of the transition layer, the TiAlSi target is directly used, which can achieve co-deposition of multiple elements with a single target, avoiding the complex process of multi-co-sputtering. By directly using the TiAlSi target, multiple elements can be evenly distributed in the target; through the gradient bias technology, the interface energy is gradually adjusted, the stress mutation is reduced, and the growth of columnar crystals is inhibited.
[0025] During the deposition of the transition layer and the surface layer in the present invention, the initial negative bias is gradually reduced to the coating bias value. Through the gradient bias technology, the interface energy is gradually adjusted, and the surface layer bias is gradually reduced to the coating bias value to remove surface impurities on the workpiece or the surface layer, form a shallow implantation, reduce the stress mutation of the workpiece and the TiAlSi surface layer material, inhibit the growth of columnar crystals, and during the deposition of the surface layer, the gas flow rate is gradually increased to the coating flow rate value, forming an effective combination of crystals and amorphous substances;
[0026] By adjusting the process parameters during the entire coating process, including the duty cycle, target voltage, gas flow rate, air pressure, temperature, etc., the prepared AlTiSiN coating shows an amorphous structure to obtain better coating properties; coatings with a dense structure can be obtained under different bias power supplies, and the coatings prepared under high bias have excellent mechanical properties, with the highest hardness reaching 16.9 GPa, and the coatings prepared under high bias are more corrosion-resistant in terms of the corrosion resistance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, the drawings in the following description are only exemplary, and for those of ordinary skill in the art, without creative efforts, other implementation drawings can be obtained according to the provided drawings.
[0028] Figure 1 It is a schematic flow chart of a method for preparing an AlTiSiN coating based on HiPIMS technology provided by the present invention.
[0029] Figure 2 XRD patterns of AlTiSiN coatings prepared by HiPIMS under different bias voltages in Examples 1 to 4 of the present invention are provided;
[0030] Figure 3 A cross-sectional view of the AlTiSiN coating prepared by HiPIMS under a bias voltage of -160V in Example 4 of the present invention is provided;
[0031] Figure 4 Variation diagrams of the hardness H and elastic modulus E of the AlTiSiN coatings prepared by HiPIMS under different bias voltages in Examples 1 to 4 of the present invention are provided. Detailed implementation manners
[0032] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.
[0033] As Figure 1 shown, the present invention provides a method for preparing an AlTiSiN coating based on HiPIMS technology, including the following steps:
[0034] The first step: Surface pretreatment of the stainless steel bipolar plate
[0035] Using the stainless steel bipolar plate as the workpiece raw material, put the stainless steel bipolar plate workpiece into ethanol and ultrasonically clean it for 10 min for pretreatment, and then dry it.
[0036] The second step: Glow cleaning of the stainless steel bipolar plate surface
[0037] First, place the pretreated sample in an argon environment, 60 mm to 160 mm away from the target surface, and evacuate the vacuum chamber to below 5*10 -3 Pa; Introduce Ar gas and adjust the gas flow rate so that the vacuum degree of the vacuum chamber is 1 Pa to 3 Pa; Apply a negative bias voltage to the workpiece holder through the bias power supply, and set the voltage parameters and cleaning time to complete the glow cleaning of the stainless steel bipolar plate surface.
[0038] Specific parameter ranges: voltage value -400V to -600V, frequency 20 kHz to 100 kHz, duty cycle 20%-80%, cleaning time 10 min - 30 min.
[0039] The third step: Deposition of the TiAlSi transition layer
[0040] Reduce the Ar gas flow rate to make the air pressure in the vacuum chamber 0.1 Pa - 1 Pa, and keep the workpiece rotating both around its own axis and in a circular motion within the chamber. Turn on the HiPIMS power supply to sputter the TiAlSi target. First, load it to the starting bias voltage value, and then gradually reduce it to the coating bias voltage value. Apply a negative bias voltage to the workpiece holder. Subsequently, the TiAlSi coating is deposited on the surface of the stainless steel bipolar plate.
[0041] The rotational speed range of the workpiece holder is: 3 - 20 rpm; the parameter range of the HiPIMS power supply:
[0042] The pulse voltage is 500 V - 700 V, the pulse frequency is 50 Hz - 200 Hz, and the duty cycle is 1% - 2%;
[0043] The specific parameter range of the bias power supply is: the bias voltage is from the starting bias voltage value - 250 V, the coating bias voltage value is - 160 V to - 10 V, the voltage reduction is in a gradient manner, the voltage reduction amplitude is 40 - 50 V, and after each voltage reduction, the unit deposition time is maintained. The pulse frequency is 20 kHz - 100 kHz, the duty cycle is 20% - 80%, and the sum of the bias voltage value drop time and the coating bias voltage value deposition time is 5 min - 10 min.
[0044] Step 4: Deposition of the N - element surface layer
[0045] Keep the bias power supply connected, gradually introduce nitrogen into the vacuum chamber to the coating nitrogen flow rate, keep the HiPIMS power supply on and the workpiece holder rotating. First, load it to the starting bias voltage value, and then gradually reduce it to the coating bias voltage value to achieve the deposition of N - element and obtain the AlTiSiN surface layer.
[0046] The rotational speed range of the workpiece holder is: 3 - 20 rpm;
[0047] The parameter range of the HiPIMS power supply: the pulse voltage is 500 V - 700 V, the pulse frequency is 50 Hz - 200 Hz, and the duty cycle is 1% - 2%;
[0048] The specific parameter range of the bias power supply is: the bias voltage is from the starting bias voltage value - 250 V, the coating bias voltage value is - 160 V to - 10 V, the voltage reduction is in a gradient manner, the voltage reduction amplitude is 40 - 50 V, and after each voltage reduction, the unit deposition time is maintained. The pulse frequency is 20 kHz - 100 kHz, the duty cycle is 20% - 80%, and the sum of the bias voltage value drop time and the coating bias voltage value deposition time is 60 min - 120 min.
[0049] The preparation steps of the present invention include: the bias voltage of the transition layer gradually decreases, the bias voltage of the surface layer gradually decreases, and the gas flow rate gradually increases to the coating flow rate value.
[0050] During the deposition of the TiAlSi transition layer and the N element surface layer, a gradient bias technology is adopted. By means of the gradient bias technology, the interface energy is gradually adjusted, the stress mutation is reduced, and the columnar crystal growth is inhibited. Specifically, the initial negative bias is gradually reduced to the coating bias value. The interface energy is gradually adjusted by the gradient bias technology, and the surface layer bias is gradually reduced to the coating bias value to remove surface impurities, form a shallow implantation, reduce the stress mutation, and inhibit the columnar crystal growth.
[0051] The total deposition time is the sum of the bias drop time and the coating bias value deposition time. In order to achieve a shallow implantation, the coating bias value deposition time should be greater than the unit deposition time. Taking the deposition of the N element surface layer as an example, when the unit deposition time is 5 min, the coating bias value deposition time is 95 min.
[0052] In fact, during the coating preparation process, the dynamic adjustment of the bias and gas flow rate will simultaneously affect parameters such as plasma density and ion energy. The process of optimizing parameters and the final performance of the coating cannot be simply predicted. Therefore, how to adjust and limit the above parameters to improve the coating performance is quite complicated.
[0053] The present invention adjusts the deposition steps of the transition layer deposition and the surface layer deposition, gradually reduces the initial negative bias to the coating bias value, gradually adjusts the interface energy by the gradient bias technology, and gradually reduces the surface layer bias to the coating bias value to remove surface impurities. During the surface layer deposition process, by gradually increasing the gas flow rate to the coating flow rate value and combining with the gradient bias technology, an effective combination of crystals and non-crystals is formed, having a prominent effect.
[0054] The AlTiSiN coating of the present invention is described below by way of examples.
[0055] Example 1
[0056] (1) Surface pretreatment of the stainless steel bipolar plate
[0057] Using the stainless steel bipolar plate as the raw material, the stainless steel bipolar plate is put into ethanol and ultrasonically cleaned for 10 min for pretreatment, and then dried.
[0058] (2) Glow cleaning of the stainless steel bipolar plate surface
[0059] First, the pretreated sample is placed in an argon environment, 100 mm away from the target surface, and the vacuum chamber is pumped to 5*10 -3Below Pa; introduce Ar gas and adjust the gas flow rate to make the vacuum degree of the vacuum chamber 1.5 Pa; apply a negative bias voltage to the workpiece holder through a bias power supply, and set the voltage parameters and cleaning time to complete the glow cleaning of the stainless steel bipolar plate surface. Specific parameters: voltage value -600 V, frequency 60 kHz, duty cycle 80%, cleaning time 20 min.
[0060] (3) Transition layer deposition
[0061] Reduce the Ar gas flow rate to make the air pressure in the vacuum chamber 0.4 Pa, and keep the workpiece rotating both around its own axis and in revolution in the chamber. Turn on the HiPIMS power supply to sputter the TiAlSi target. Apply a negative bias voltage to the workpiece holder, and then the TiAlSi coating is deposited on the stainless steel bipolar plate surface.
[0062] The rotation speed of the workpiece holder is: 18 rpm;
[0063] The parameters of the HiPIMS power supply: pulse voltage 650 V, pulse frequency 100 Hz, duty cycle 1%;
[0064] The specific parameter range of the bias power supply is: apply -250 V → gradually decrease to -10 V, the bias voltage value drops in 5 min (-250 V is maintained for 1 min, -200 V is maintained for 1 min, -150 V is maintained for 1 min, -100 V is maintained for 1 min, -50 V is maintained for 1 min), the deposition time at the coating bias voltage value of -10 V is 3 min, pulse frequency 60 kHz, duty cycle 80%.
[0065] (4) Surface layer deposition
[0066] Gradually introduce nitrogen until the nitrogen flow rate for coating is 25 sccm and the argon flow rate is 130 sccm to deposit the AlTiSiN surface layer.
[0067] The rotation speed of the workpiece holder is: 18 rpm;
[0068] The parameters of the HiPIMS power supply are: pulse voltage 650 V, pulse frequency 100 Hz, duty cycle 1%;
[0069] The specific parameters of the bias power supply are: apply -250 V → gradually decrease to -10 V, the decreasing speed of the bias voltage value is 50 V / min, pulse frequency 60 kHz, duty cycle 80%, the bias voltage value drops in 5 min (250 V is maintained for 1 min, 200 V is maintained for 1 min, 150 V is maintained for 1 min, 100 V is maintained for 1 min, 50 V is maintained for 1 min), the deposition time at the coating bias voltage value of -10 V is 95 min.
[0070] Example 2
[0071] (1) Surface pretreatment of stainless steel bipolar plate
[0072] Taking the stainless steel bipolar plate as the raw material, put the stainless steel bipolar plate into ethanol and ultrasonically clean it for 10 min for pretreatment, and then dry it.
[0073] (2) Glow cleaning of the surface of the stainless steel bipolar plate
[0074] First, place the pretreated sample in an argon environment, 100 mm away from the target surface, and evacuate the vacuum chamber to below 5×10 -3 Pa; introduce Ar gas and adjust the gas flow rate so that the vacuum degree of the vacuum chamber is 1.5 Pa; apply a negative bias voltage to the workpiece holder through the bias power supply, and set the voltage parameters and cleaning time to complete the glow cleaning of the surface of the stainless steel bipolar plate.
[0075] The specific parameters are: voltage value -600 V, frequency 60 kHz, duty cycle 80%, cleaning time 20 min.
[0076] (3) Transition layer deposition
[0077] Reduce the Ar gas flow rate to make the air pressure in the vacuum chamber 0.4 Pa, and keep the workpiece rotating both around its own axis and revolving in the chamber. Turn on the HiPIMS power supply to sputter the TiAlSi target. Apply a negative bias voltage to the workpiece holder, and then the TiAlSi coating is deposited on the surface of the stainless steel bipolar plate.
[0078] Among them, the rotation speed of the workpiece holder is: 18 rpm;
[0079] The parameters of the HiPIMS power supply: pulse voltage is 650 V, pulse frequency is 100 Hz, duty cycle is 1%;
[0080] The specific parameters of the bias power supply are: apply -250 V → gradually decrease to -60 V, the decreasing speed of the bias voltage value is 50 V / min, pulse frequency is 60 kHz, duty cycle is 80%, the decreasing time of the bias voltage value is 4 min (-250 V is maintained for 1 min, -200 V is maintained for 1 min, -150 V is maintained for 1 min, -100 V is maintained for 1 min), and the deposition time of the coating bias voltage value of -60 V is 4 min.
[0081] (4) Surface layer deposition
[0082] Gradually introduce nitrogen gas until the nitrogen gas flow rate for coating is 25 sccm and the argon gas flow rate is 130 sccm to deposit the AlTiSiN surface layer.
[0083] Among them, the rotation speed of the workpiece holder is: 18 rpm;
[0084] Parameters of the HiPIMS power supply: pulse voltage is 650V, pulse frequency is 100Hz, and duty cycle is 1%;
[0085] Specific parameters of the bias power supply are as follows: load -250V → gradually decrease to -60V, the decreasing speed of the bias voltage value is 50V / min, pulse frequency is 60kHz, duty cycle is 80%, the time for the bias voltage value to decrease is 4min (-250V is maintained for 1min, -200V is maintained for 1min, -150V is maintained for 1min, -100V is maintained for 1min), and the deposition time of the coating bias voltage value of -60V is 96min.
[0086] Example 3
[0087] (1) Surface pretreatment of the stainless steel bipolar plate
[0088] Using the stainless steel bipolar plate as the raw material, put the stainless steel bipolar plate into ethanol and ultrasonically clean it for 10min for pretreatment, and then dry it.
[0089] (2) Glow cleaning of the surface of the stainless steel bipolar plate
[0090] First, place the pretreated sample in an argon environment, 100mm away from the target surface, and pump the vacuum chamber to below 5*10 -3 Pa; introduce Ar gas and adjust the gas flow rate so that the vacuum degree of the vacuum chamber is 1.5Pa; apply a negative bias voltage to the workpiece holder through the bias power supply, and set the voltage parameters and cleaning time to complete the glow cleaning of the surface of the stainless steel bipolar plate.
[0091] Specific parameters: voltage value -600V, frequency 60kHz, duty cycle 80%, cleaning time 20min.
[0092] (3) Deposition of the transition layer
[0093] Reduce the Ar gas flow rate to make the air pressure in the vacuum chamber 0.4Pa, and keep the workpiece rotating both around its own axis and revolving in the chamber. Turn on the HiPIMS power supply to sputter the TiAlSi target. Apply a negative bias voltage to the workpiece holder, and then the TiAlSi coating is deposited on the surface of the stainless steel bipolar plate.
[0094] The rotation speed of the workpiece holder is: 18rpm;
[0095] Parameters of the HiPIMS power supply: pulse voltage is 650V, pulse frequency is 100Hz, and duty cycle is 1%;
[0096] The specific parameters of the bias power supply are as follows: load -250V → gradually decrease to -110V, the decreasing speed of the bias value is 50V / min, the pulse frequency is 60kHz, the duty cycle is 80%, the decreasing time of the bias value is 3min (-250V is maintained for 1min, -200V is maintained for 1min, -150V is maintained for 1min), the deposition time of the coating bias value of -110V is 5min, and the deposition time of the coating bias value is 5min.
[0097] (4) Surface layer deposition
[0098] Gradually introduce nitrogen gas until the nitrogen gas flow value for coating is 25sccm, and the argon gas flow value is 130sccm to deposit the AlTiSiN surface layer.
[0099] Among them, the rotation speed of the workpiece holder is: 18rpm;
[0100] The parameters of the HiPIMS power supply: the pulse voltage is 650V, the pulse frequency is 100Hz, and the duty cycle is 1%;
[0101] The specific parameters of the bias power supply are as follows: load -250V → gradually decrease to -110V, the decreasing speed of the bias value is 50V / min, the pulse frequency is 60kHz, the duty cycle is 80%, the decreasing time of the bias value is 3min (-250V is maintained for 1min, -200V is maintained for 1min, -150V is maintained for 1min), and the deposition time of the coating bias value of -110V is 97min.
[0102] Example 4
[0103] (1) Surface pretreatment of the stainless steel bipolar plate
[0104] Using the stainless steel bipolar plate as the raw material, put the stainless steel bipolar plate into ethanol and ultrasonically clean it for 10min for pretreatment, and then dry it.
[0105] (2) Glow cleaning of the stainless steel bipolar plate surface
[0106] First, place the pretreated sample in an argon environment, 100mm away from the target surface, and evacuate the vacuum chamber to below 5*10 -3 Pa; Introduce Ar gas and adjust the gas flow rate so that the vacuum degree of the vacuum chamber is 1.5Pa; Apply a negative bias voltage to the workpiece holder through the bias power supply, and set the voltage parameters and cleaning time to complete the glow cleaning of the stainless steel bipolar plate surface.
[0107] Specific parameters: voltage value -600V, frequency 60kHz, duty cycle 80%, cleaning time 20min.
[0108] (3) Transition layer deposition
[0109] Reduce the Ar gas flow rate to make the air pressure in the vacuum chamber 0.4 Pa, and keep the workpiece rotating both around its own axis and in a circular motion within the chamber. Turn on the HiPIMS power supply to sputter the TiAlSi target. Apply a negative bias voltage to the workpiece holder, and then a TiAlSi coating is deposited on the surface of the stainless steel bipolar plate.
[0110] The rotation speed range of the workpiece holder is: 18 rpm;
[0111] The parameters of the HiPIMS power supply: the pulse voltage is 650 V, the pulse frequency is 100 Hz, and the duty cycle is 1%;
[0112] The specific parameters of the bias power supply are: apply -250 V → gradually decrease to -160 V, the decreasing speed of the bias voltage value is 50 V / min, the pulse frequency is 60 kHz, the duty cycle is 80%, the decreasing time of the bias voltage value is 2 min (-250 V is maintained for 1 min, -200 V is maintained for 1 min), and the deposition time at the coating bias voltage of -160 V is 6 min.
[0113] (4) Surface layer deposition
[0114] Gradually introduce nitrogen until the nitrogen flow rate value for coating is 25 sccm and the argon flow rate value is 130 sccm to deposit the AlTiSiN surface layer.
[0115] The rotation speed of the workpiece holder is: 18 rpm;
[0116] The parameters of the HiPIMS power supply: the pulse voltage is 650 V, the pulse frequency is 100 Hz, and the duty cycle is 1%;
[0117] The specific parameters of the bias power supply are: apply -250 V → gradually decrease to -160 V, the decreasing speed of the bias voltage value is 50 V / min, the pulse frequency is 60 kHz, the duty cycle is 80%, the decreasing time of the bias voltage value is 2 min (-250 V is maintained for 1 min, -200 V is maintained for 1 min), and the deposition time at the coating bias voltage of -160 V is 98 min.
[0118] In Examples 1 to 4, the difference lies in the bias voltage of the bias power supply in the two sputtering steps of the transition layer deposition and the surface layer deposition.
[0119] Characterize Examples 1 - 4:
[0120] Observe the cross-sectional characteristics of the coating with a field emission scanning electron microscope (FE-SEM, SUPRA 55, ZEISS, Germany), and measure the surface composition of the coating with an energy spectrometer.
[0121] Determine the crystal structure of the coating with an X-ray diffractometer (XRD, D8 Discover, Bruker, America).
[0122] The CHI660C electrochemical workstation from Shanghai Chenhua was selected to conduct electrochemical corrosion tests on the coatings in a 1 mol / L H2SO4 solution.
[0123] The corrosion current density of the AlTiSiN coatings is shown in Table 1:
[0124] Table 1
[0125]
[0126]
[0127] Table 1 shows that the corrosion current density of all AlTiSiN coatings is several orders of magnitude smaller than that of the substrate, and the corrosion current density is less than 1 μA / cm 2 , indicating excellent corrosion resistance.
[0128] Figure 2 XRD patterns of the coating materials in Examples 1 to 4 Figure 2 show that there is only one broad peak in the XRD of the above examples, indicating the successful preparation of an amorphous structure coating.
[0129] Figure 3 Cross-sectional view of the AlTiSiN coating prepared by HiPIMS under a -160 V bias voltage Figure 3 shows that the coating structure prepared in Example 4 is dense.
[0130] Figure 4 Variation diagrams of the hardness H and elastic modulus E of the AlTiSiN coatings prepared by HiPIMS at different bias voltages in Examples 1 to 4 Figure 4 show that with the increase of the negative bias voltage, both the hardness and the elastic modulus increase with the bias voltage, and the maximum hardness can reach 16.9 GPa. It can be seen that both the hardness H and the elastic modulus E of the AlTiSiN amorphous coating prepared by HiPIMS have been significantly improved, indicating that the coating has excellent mechanical properties.
[0131] As can be seen from the above embodiments, directly using a TiAlSi target in the deposition of the transition layer can achieve co-deposition of multiple elements with a single target, avoiding the complex process of multi-cosputtering. By directly using a TiAlSi target, multiple elements can be evenly distributed in the target. By means of the gradient bias technology, the interface energy is gradually adjusted, the stress mutation is reduced, and the growth of columnar crystals is inhibited. By adjusting the process parameters during the entire coating process, including the duty cycle, target voltage, gas flow rate, air pressure, temperature, etc., the prepared AlTiSiN coating exhibits an amorphous structure to obtain better coating properties. Dense coatings can be obtained under different bias power supplies, and the coatings prepared under high bias have excellent mechanical properties, with the highest hardness reaching 16.9 GPa. In terms of the corrosion resistance of the coating, the coatings prepared under high bias are more corrosion-resistant.
[0132] The above embodiments are only exemplary embodiments of the present application and are not used to limit the present application. The protection scope of the present application is defined by the claims. Those skilled in the art can make various modifications or equivalent replacements to the present application within the essence and protection scope of the present application, and such modifications or equivalent replacements should also be regarded as falling within the protection scope of the present application.
Claims
1. A method for preparing an AlTiSiN coating based on HiPIMS technology, characterized in that, It includes the following steps: Perform glow cleaning on the surface of the workpiece; While the workpiece rotates around its axis and revolves within the cavity, sputter the TiAlSi target onto the workpiece by HiPIMS. First, load the workpiece to the starting bias voltage value through a bias power supply, and then gradually reduce the starting bias voltage value to the coating bias voltage value through the first voltage reduction treatment. A TiAlSi surface layer is deposited on the surface of the workpiece to complete the deposition of the transition layer; Keep the workpiece rotating, gradually introduce nitrogen into the vacuum cavity to the coating flow rate value. First, load the workpiece to the starting bias voltage value through a bias power supply, and then gradually reduce the starting bias voltage value to the coating bias voltage value through the second voltage reduction treatment. N elements are deposited onto the TiAlSi surface layer to complete the deposition of the surface layer, so as to obtain an AlTiSiN coating.
2. A method for preparing an AlTiSiN coating based on HiPIMS technology according to claim 1, characterized in that In the first voltage reduction treatment, the starting bias voltage value is -250V, and the coating bias voltage value is -160V to -10V.
3. A method for preparing an AlTiSiN coating based on HiPIMS technology according to claim 2, characterized in that The first voltage reduction treatment is a gradient voltage reduction, and the voltage reduction amplitude of the gradient voltage reduction is 40 - 50V; In each gradient pressure, the unit deposition time is maintained; The deposition time of the coating bias voltage value is greater than the unit deposition time.
4. A method for preparing an AlTiSiN coating based on HiPIMS technology according to claim 1, characterized in that In the second voltage reduction treatment, the starting bias voltage value is -250V, and the coating bias voltage value is -160V to -10V.
5. A method for preparing an AlTiSiN coating based on HiPIMS technology according to claim 4, characterized in that The second voltage reduction treatment is a gradient voltage reduction, and the voltage reduction amplitude of the gradient voltage reduction is 40 - 50V; In each gradient pressure, the unit deposition time is maintained; The deposition time of the coating bias voltage value is greater than the unit deposition time.
6. A method for preparing an AlTiSiN coating based on HiPIMS technology according to claim 1, characterized in that, In the coating flow rate value, the nitrogen flow rate value is 25 sccm.
7. A method for preparing an AlTiSiN coating based on HiPIMS technology according to claim 1, characterized in that The glow cleaning includes the following steps: Place the preliminarily cleaned workpiece in an argon environment, 60 mm to 160 mm away from the target surface. Introduce argon to make the vacuum degree of the vacuum cavity 1 Pa to 3 Pa. Apply a negative bias voltage to the workpiece holder for clamping the workpiece through a bias power supply, and set the voltage parameters and cleaning time to complete the glow cleaning of the workpiece surface.
8. A method for preparing an AlTiSiN coating based on HiPIMS technology according to claim 7, characterized in that In the glow cleaning step, the specific parameter range of the bias power supply is: the voltage value is -400V to -600V, the frequency is 20 kHz to 100 kHz, and the duty cycle is 20% - 80%; The cleaning time is 10 min - 30 min.
9. A method for preparing an AlTiSiN coating based on HiPIMS technology according to claim 8, characterized in that in the glow cleaning step, the specific parameter range of the bias power supply is: the voltage value is -600V, the frequency is 60kHz, and the duty cycle is 80%; the cleaning time is 20 minutes.